The Routledge handbook of anti-corruption research and practice - Pozsgai-Alvarez, Joseph; Bratu, Roxana (Routledge international handbooks, 2025)
"The Routledge Handbook of Anti-Corruption Research and Practice" takes a multidisciplinary and multidimensional approach to provide a comprehensive exploration of the processes, conditions, and activities that hold the potential to control corruption. Building on existing knowledge gathered from a variety of social science sources, it strives to provide analytical emancipation of, and coherence to, anti-corruption studies. Anti-corruption transcends the traditional boundaries of state actors, involving individual and organizational business actors, civil society groups, members of the media, accounting, and legal professions, as well as sports associations and other non-traditional actors. This handbook adopts a holistic approach to reflect the rich nature of the manifestations of anti-corruption - past and present - and the possible shapes it may still take in the future. This handbook is a key reference for scholars, students and practitioners engaged in the study and practice of anti-corruption, corruption, democracy, public administration, comparative politics as well as more broadly to the wider social sciences